2012
DOI: 10.1124/mol.112.080440
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Agonists Mediate Enhancement of β1-Adrenergic Receptor N-terminal Cleavage and Stabilization In Vivo and In Vitro

Abstract: The b 1 -adrenergic receptor (b 1 AR) is the predominant bAR in the heart and is the main target for b-adrenergic antagonists, widely used in the treatment of cardiovascular diseases. Previously, we have shown that the human (h) b 1 AR is cleaved in its N terminus by a metalloproteinase, both constitutively and in a receptor activation-dependent manner. In this study, we investigated the specific events involved in b 1 AR regulation, focusing on the effects of long-term treatment with b-adrenergic ligands on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Imai et al, 2001) is very similar to that of the human receptor, in line with the present observations. This implies that the cleavage of GPR37 is evolutionarily conserved in a similar manner as has been demonstrated for ET B R (Kozuka et al, 1991;Grantcharova et al, 2002) and the β 1 adrenergic receptor (Hakalahti et al, 2013). Interestingly, one of the studies aiming to enhance GPR37 plasma membrane trafficking demonstrated that the receptor cell surface expression could be increased significantly by N-terminal truncations (Dunham et al, 2009).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Imai et al, 2001) is very similar to that of the human receptor, in line with the present observations. This implies that the cleavage of GPR37 is evolutionarily conserved in a similar manner as has been demonstrated for ET B R (Kozuka et al, 1991;Grantcharova et al, 2002) and the β 1 adrenergic receptor (Hakalahti et al, 2013). Interestingly, one of the studies aiming to enhance GPR37 plasma membrane trafficking demonstrated that the receptor cell surface expression could be increased significantly by N-terminal truncations (Dunham et al, 2009).…”
Section: Discussionmentioning
confidence: 73%
“…In addition to ET B R, the cleavage of β 1 adrenergic and V 2 vasopressin receptors has been reported to occur in an activationdependent manner following ligand binding (Kojro and Fahrenholz, 1995;Hakalahti et al, 2010Hakalahti et al, , 2013. A similar mechanism has been implicated for TSHR (Latif et al, 2004;Kaczur et al, 2007), although conflicting information exists (Chazenbalk et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…We have shown previously that ␤ 1 AR undergoes limited N-terminal cleavage by metalloproteinases in heterologous expression systems as well as in vivo in rat neonatal cardiomyocytes (5,6), indicating that limited proteolysis has a regulatory function in receptor downregulation. We identified two cleavage sites for the human receptor at positions 31 N terminus and demonstrated that the cleavage at the major site 31 R2L 32 is augmented by agonist-mediated activation of the receptor (5,6). We also found that ␤ 1 AR undergoes GalNActype O-glycosylation (hereafter simply referred to as O-glycosylation) (5), and the NetOGlyc4.0 prediction algorithm predicts the presence of five O-glycan sites in the receptor N-terminal extracellular sequence (7).…”
mentioning
confidence: 90%
“…The resulting partial loss of ␤ 1 AR function is believed to be an adaptive mechanism to counteract the cardiotoxicity of chronic adrenergic signaling (4). We have shown previously that ␤ 1 AR undergoes limited N-terminal cleavage by metalloproteinases in heterologous expression systems as well as in vivo in rat neonatal cardiomyocytes (5,6), indicating that limited proteolysis has a regulatory function in receptor downregulation. We identified two cleavage sites for the human receptor at positions 31 N terminus and demonstrated that the cleavage at the major site 31 R2L 32 is augmented by agonist-mediated activation of the receptor (5,6).…”
mentioning
confidence: 99%
“…Gels containing radiolabeled samples were treated with EN3HANCE (PerkinElmer Life Sciences), dried, and exposed at Ϫ70°C for 1-21 days using the Biomax MR film (Eastman Kodak) and intensifying screens. The films were analyzed by densitometric scanning with the Umax PowerLook 1120 color scanner (GE Healthcare) or the Agfa Arcus II laser scanner, and quantified as described (30).…”
Section: Methodsmentioning
confidence: 99%